El Programa Azahar de fomento del desarrollo sostenible en la cuenca del Mediterráneo y sus iniciativas en materia de energías renovables - Ferré, Josep (Revista Española de Desarrollo y Cooperación, 2023)
This article presents the Program Azahar of Promotion of the Sustainable Development in the River basin of the Mediterranean sea and its main features like its structure, the geographic and sectoral scope and mechanisms of performance. It finishes by making a balance of the performances made until the moment, mainly projects and seminaries with particular reference to those dealing with renewable energies.